Identification of Gangliosides GD1b and GT1b as Receptors for BK Virus - Low, Jonathan A. (American Society for Microbiology, 2006)
Gangliosides have been shown to be plasma membrane receptors for both murine polyomavirus and SV40, while JC virus uses serotonin receptors. In contrast, little is known of the membrane receptor and entry pathway for BK virus (BKV), which can cause severe disease in immunosuppressed bone marrow and renal transplant patients. Using sucrose flotation assays, we investigated BKV binding to and interaction with human erythrocyte membranes and determined that this interaction was dependent on a neuraminidase-sensitive, proteinase K-resistant molecule. BKV was found to interact with the gangliosides GT1b and GD1b. The terminal α2-8-linked disialic acid motif, present in both of these gangliosides, is likely to be important for this interaction. We also determined that the addition of GD1b and GT1b to LNCaP cells, which are normally resistant to BKV infection, made them susceptible to the virus. In addition, BKV interacted with membranes extracted from the endoplasmic reticulum (ER) and infection was blocked by the addition of brefeldin A, which interferes with transport from the ER to the Golgi apparatus. These data demonstrate that BKV uses the gangliosides GT1b and GD1b as receptors and passes through the ER on the way to the nucleus.